2013
DOI: 10.1186/1687-5281-2013-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel coarse-to-fine dual scale technique for tuberculosis cavity detection in chest radiographs

Abstract: Although many lung disease diagnostic procedures can benefit from computer-aided detection (CAD), current CAD systems are mainly designed for lung nodule detection. In this article, we focus on tuberculosis (TB) cavity detection because of its highly infectious nature. Infectious TB, such as adult-type pulmonary TB (APTB) and HIV-related TB, continues to be a public health problem of global proportion, especially in the developing countries. Cavities in the upper lung zone provide a useful cue to radiologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…This method is the first automatic algorithm that detects tuberculosis accurately but uses a global adaptive threshold in such a way that automatic initialization cannot place the initial contour within the cavity, leaving a cavity. Xu et al [89] classified tuberculosis cavities by combining texture and geometric features. First, rough feature classification was performed using Gaussian model-based template matching (GTM), LBP, and directional gradient histogram (HOG) methods to extract cavity candidates from CXR images.…”
Section: Specific Disease Detectionmentioning
confidence: 99%
“…This method is the first automatic algorithm that detects tuberculosis accurately but uses a global adaptive threshold in such a way that automatic initialization cannot place the initial contour within the cavity, leaving a cavity. Xu et al [89] classified tuberculosis cavities by combining texture and geometric features. First, rough feature classification was performed using Gaussian model-based template matching (GTM), LBP, and directional gradient histogram (HOG) methods to extract cavity candidates from CXR images.…”
Section: Specific Disease Detectionmentioning
confidence: 99%
“…If we compare our results with the state of the art, [14][15][16] we achieved higher overlap on a substantially larger number of CXRs (100) containing 126 cavities than what has been reported in the literature (on 50 and 20 cavities). Analysis of the manual segmentations revealed that there were multiple cases where the human readers exhibited large disagreement.…”
Section: Discussionmentioning
confidence: 50%
“…Shen et al did not report the accuracy of their contour segmentation of the cavities. Another automatic cavity detection system was presented by Xu et al 14 based on a coarse-to-fine dual scale methodology, where simpler features, such as Gaussianbased matching and local binary patterns, were applied at a coarse scale, while complex features, such as circularity and Kullback-Leibler divergence measures, were applied on a finer scale for the cavity classification. This method was validated on 35 CXRs containing 50 cavities and reported an average Tanimoto overlapping degree of 67.1%.…”
Section: Introductionmentioning
confidence: 99%
“…The particular organ which attacked by toberculosis is the lung, which is known as lung tuberculosis [1]. Early detection is urgently needed during the treatment on TB lung patient.…”
Section: Introductionmentioning
confidence: 99%